The features of support of social activity of older people - Helen Piontkіvs'ka (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article is devoted to the features of support of social activity of older people. The need for research is determined to the fact that the questions of support and development of social activity of the elderly are relevant, but not explored. The article analyzes the main approaches to the definition of the social activity of the individual, and identifies possible ways to support social activity of elderly.
Keywords: social activity of the person; public activity; older age